The Analysis of Road Traffic Accidents in the Last 20 Years in Slovenia (Journal of Universal Excellence, 2026)
Research Question (RQ): How many road traffic accidents have happened in the last 20 years, which are the key risk factors, when and where are they most likely to happen, and what are the consequences?Purpose: To provide a historical overview of road traffic accidents for the last 20 years and determine how the key risk factors have changed over this period of time. We want to predict future trends and make recommendations for road safety.Method: The frequency statistics were used for analysis; results are shown in tables and graphs.Results: The number of road accidents and the number of fatal road accidents is decreasing. The most important cause of road accidents is speeding.Organization: Based on the results of the survey, the Ministry of the Interior as well as governmental and non-governmental organizations will be able to manage their activities in the field of road traffic safety more effectively and efficiently.Society: The social costs of road traffic accidents will be reduced by safety improvements.Originality: The research is a comprehensive overview of road accidents that occurred between 1997 and 2016.Limitations/Future Research: The year 2017 is excluded from research because data is not available. The role of alcohol as a risk factor as well as types of people involved in road accidents must be investigated.
Keywords: traffic; road safety; traffic accidents; injury; death; risk factors